The dynamics of the studies of China’s science, technology and innovation (STI): a bibliometric analysis of an emerging field - Sun, Yutao; Cao, Cong (Springer, 2020)
Since 1978, alongside China’s rise as a leading country in science, technology and innovation (STI), the studies of the country’s STI have been emerging as a field attracting increasing scholarly attention. Using the bibliometric method and the data from the Web of Science (WoS), this paper seeks to provide a comprehensive picture of the studies of China’s STI. The findings show that scholarly interests in China’s STI started in 1995 and have since developed rapidly; institutions in China, the U.S. and the U.K. are main contributors to the field, contributing 50%, 27.2% and 12% of the scholarship respectively, with Tsinghua University, Zhejiang University and the Chinese Academy of Sciences being three major institutional contributors. Seminal works have been focused on STI issues at the macro or national, meso or industrial and regional, and micro or organizational and firm levels. A possible agenda for further research is to develop new theories based on China’s practice paying specific attention to issues including R&D expenditure, S&T performance evaluation, regional innovation ecosystem, SOEs in innovation and the role of the Chinese Communist Party in innovation.